Brazil and the economic, political, and environmental multilateralism: the Lula years (2003-2010) - Visentini,Paulo G. Fagundes (2010)
This article discusses Brazil's multilateral policy under Luiz Inácio Lula da Silva's administration, highlighting economic, political and environmental themes. The main argument is that Brazil's multilateral relations during this government reached a new significance with the reinforcement of international coalitions and the articulation with the country's new development model. The country has been using multilateral forums as a way to achieve international projection and support for its development project, highlighting bargaining aspects, variable geometry coalitions and the strengthening of South-South cooperation